2015
DOI: 10.1536/ihj.15-133
|View full text |Cite
|
Sign up to set email alerts
|

KCNN3 SNP rs13376333 on Chromosome 1q21 Confers Increased Risk of Atrial Fibrillation

Abstract: SummaryTo investigate the relationship between KCNN3 SNP (single-nucleotide polymorphism) rs13376333 and risk of atrial fibrillation (AF) and to provide evidence for prevention and treatment for AF.The PubMed, Embase, OVID, Cochrane library, CNKI, and Wan Fang databases were searched to identify studies on the relationship between KCNN3 SNP rs13376333 polymorphism and atrial fibrillation. Two authors performed independent article reviews and study quality assessment using the Newcastle-Ottawa Scale (NOS) check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[30] ZFHX3 knockdown in atrial myocytes dysregulated calcium homeostasis and increased atrial arrhythmogenesis, ultimately contributing to AF occurrence. [31] Studies found rs13376333, rs7193343, and rs2106261 increased risk of AF [3234] and some studies also involved in their relationship on AF recurrence. [3,4,23,35] Therefore, we also pooled the HRs of rs13376333, rs7193343, and rs2106261 variants on AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[30] ZFHX3 knockdown in atrial myocytes dysregulated calcium homeostasis and increased atrial arrhythmogenesis, ultimately contributing to AF occurrence. [31] Studies found rs13376333, rs7193343, and rs2106261 increased risk of AF [3234] and some studies also involved in their relationship on AF recurrence. [3,4,23,35] Therefore, we also pooled the HRs of rs13376333, rs7193343, and rs2106261 variants on AF recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…22) Previous studies have documented that in some familial AF patients, novel susceptibility genes are responsible for electrical abnormalities leading to AF in the absence of structural remodeling. [23][24][25][26][27][28] These specific genes are related to the many channelopathies present in both the atria and ventricles via gain-of-function or loss-of-function of specific ion currents.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported by several studies that there are significant associations between the single nucleotide polymorphism rs13376333 in KCNN3 on chromosome 1q21 and the risk of developing AF in Chinese and European ancestry [36][37][38]. Moreover, atrial miRNA-499, an important regulator of KCNN3 gene expression, was upregulated by 2.33-fold in atria with AF, resulting in downregulation of SK3 protein expression by 46% [39].…”
Section: Figurementioning
confidence: 99%